Knowledge-driven innovation in start-ups and SMEs emerging research and opportunities - Sousa, Joana Coutinho de, 1986- (Advances in business strategy and competitive advantage., 2019)
"This book addresses several topics in the discipline of business articulated with the discipline of innovation. It presents a new approach for innovation process for start-ups, providing information about all steps that must be followed. It also presents a method for evaluating the time of the innovation process based on five porter's forces"--